Why a feminist ethics of care and socio-ecological justice lens matter for global, interdisciplinary research on water security - Narayanaswamy, Lata; Ferritto, Robert; Hillesland, Marya; Anker, Victoria; Singhal, Shivani; Maysels, Rachael Marjorie; Bantider, Amare; Charles, Katrina; Doss, Cheryl; Kumar, Ashok; Mdee, Anna; Neo, Sau-Mei; et al. (Frontiers in Human Dynamics, 2023)
In this perspectives piececonceptual analysis, we set out some of the negotiations and tensions that emerge when we try to build a shared understanding of water (in)security through the dual lenses of a feminist ethics of care and socio-ecological justice. We further reflect on how these theoretical lenses shape our work in practice -how do we actualise them in an international, interdisciplinary partnership? We actively seek to engage all our colleagues in how we understand the function of power and inequality in relation to the distribution of water resources and the ways in which intersectional inequalities shape access to, and availability of, water. We conclude that our international partnership will only add value to our understanding of water (in)security if we are able to identify not just how intersectional inequalities circumscribe differential access to water itself in a range of diverse contexts, but the ways socio-ecological justice and a feminist ethics of care are understood and in turn shape how we work together to achieve greater water security across diverse contexts.